Motivational drivers and the effectiveness of conservation incentives - Nyanghura, Qambemeda M.; Börner, Jan; Biber-Freudenberger, Lisa (Frontiers in Sustainable Food Systems, 2024)
The debate about how external incentives (e.g., payments for ecosystem services) and internal motivations (e.g., intrinsic values) interact in producing conservation outcomes is still unresolved. This paper examines the role of personal values (biospheric and egoistic) as intrinsic motivational drivers for conservation and their potential to affect conditional payments to enhance conservation behavior. We used a lab-in-the-field experiment with rural farmers in two ecological corridors of Tanzania to assess their conservation behavior under two payment modalities, namely a fixed individual payment and a fixed individual payment with an agglomeration bonus. In addition, a post-experiment survey was conducted to determine the levels of personal value endorsement for each individual participant. We consistently found that biospheric values increased conservation behavior, while egoistic values decreased it. The positive effect of biospheric values was higher than the negative effect of egoistic values. Both payments do not seem to affect the conservation behavior of farmers with high biospheric value endorsement. Heterogeneity in personal values thus likely has economic implications for the design of real-world PES schemes. Our results suggest that educational investments in training future generations of farmers with strong pro-environmental values can reduce future pressure on the environment and the costs of associated policy action. Areas for further research are discussed.